Assessing Industry Risk by Ratio Analysis: Validation. - Falk, Haim; Gordon, Lawrence A. (The Accounting Review, 1978)
In a recent comment on Haim Falk and James A. Heintz's paper, Edward Blocher and Kung H. Chen re-emphasized the need for validation of the Falk and Heintz (F&H) proposed model and the application of Guttman's scalogram technique for risk analysis of equity securities. The purpose of this paper is to assess empirically the validity of F&H's model. Thus, 459 corporations were graded according to F&H's composite risk measure. This grading was then compared with three market-based risk measures. The market-based risk measures were derived by utilizing Sharpe's capital asset pricing model. The Standard and Poor 400 industrial index served as the basis for calculating the return on all capital assets in the market. In light of the additional effort and resources needed to adjust a traditional market price index for dividends, some researchers have ignored the dividend figures in measuring the market risk. While F&H's model gained substantial support on the company dimension, the usefulness of the industry factor has been found effective only if weak monotonic relationships are acceptable.